DHA Protects Against Hepatic Steatosis by Activating Sirt1 in a High Fat Diet-Induced Nonalcoholic Fatty Liver Disease Mouse Model - Luo X (Dove Medical Press, 2020)
Xiao Luo, 1, 2,* Zhangya He, 1, 3,* Xiaomin Sun, 1, 3 Xinqian Gu, 1, 3 Wanyu Zhang, 1, 3 Jiayi Gao, 1, 3 Xiaomin Li, 1, 3 Ru Jia, 4 Junxiang Wei, 5 Yan Yu, 1, 3 Xiaoqin Luo 1, 3 1Department of Nutrition and Food Safety, School of Public Health, Xi’an Jiaotong University, Xi’an 710061, People’s Republic of China; 2Department of Physiology and Pathophysiology, School of Basic Medical Sciences, Xi’an Jiaotong University Health Science Center, Xi’an 710061, People’s Republic of China; 3Nutrition and Food Safety Engineering Research Center of Shaanxi Province, School of Medicine, Xi’an Jiaotong University, Xi’an 710061, People’s Republic of China; 4Department of Prosthodontics, Stomatological Hospital, College of Stomatology, Xi’an Jiaotong University, Xi’an 710061, People’s Republic of China; 5Department of Epidemiology and Health Statistics, School of Public Health, Xi’an Jiaotong University, Xi’an 710061, People’s Republic of China *These authors contributed equally to this workCorrespondence: Xiaoqin LuoDepartment of Nutrition and Food Safety, School of Public Health, Xi’an Jiaotong University, Xi’an 710061, People’s Republic of ChinaTel/Fax +86-29-82655111Email luoxiaoqin2012@mail.xjtu.edu.cnAim: Docosahexaenoic acid (DHA; C22; n-3) shows beneficial effects on Non-alcoholic fatty liver disease (NAFLD). Deacetylase Sirtuin1 (Sirt1) was reported to increase energy metabolism and decrease lipogenesis. Here, we investigated whether DHA plays a role in protecting against hepatic steatosis via Sirt1.Main Methods: Both in vivo and in vitro hepatic steatosis models were used: diet-induced obesity (DIO) model (middle-aged C57BL/6 mice fed a high-fat diet (HFD)) and palmitic acid (PA)-induced lipid accumulation cell model (HepG2 cells).Key Findings: In DIO mice, treatment with DHA (gavage supplementation) for 8 weeks not only inhibited the lipid accumulation, but also increased fatty acids (FA) oxidation and induced triglyceride export in liver. These changes were accompanied by attenuation of inflammation. Moreover, DHA reversed the HFD-induced reduction of Sirt1 in liver. Interestingly, the beneficial effects of DHA were reversed by lentivirus-mediated Sirt1 knockdown, accompanied with increased expression of markers of lipogenesis, inflammation and reduced FA oxidation. In HepG2 cells, DHA prevented the accumulation of PA-induced lipid droplets, the decrease of FA oxidation and the reduction of Sirt1 level. Inhibition of Sirt1 by sirtinol partially reversed the beneficial effects of DHA on PA-treated cells.Significance: DHA alleviated hepatic steatosis and reduced inflammation of liver in obese middle-aged mice by mechanisms involving Sirt1 activation.Keywords: non-alcoholic fatty liver disease, steatosis, docosahexaenoic acid, high-fat diet, Sirt1